Do Transgender People Respond According to Their Biological Sex or Their Gender Identity When Confronted With Romantic Rivals?. (17th May 2019) - Arístegui, Inés; Solano, Alejandro Castro; Buunk, Abraham P.
This study examined the hypothesis that gender identity and biological sex represent independent modules and that transgender individuals respond to romantic rivals in line with their gender identity and not with their biological sex. Additionally, associations of jealousy with intrasexual competitiveness (ISC) and social comparison orientation (SCO) were explored. A total of 134 male-to-female and 94 female-to-male transgender individuals from Greater Buenos Aires, Argentina, responded to a questionnaire. In line with the predictions, female-to-male transgender individuals experienced more jealousy than male-to-female transgender individuals in response to a physically dominant rival, whereas male-to-female individuals experienced more jealousy than female-to-male individuals in response to a physically attractive rival. Regardless of their gender identity, in both groups social-communal attributes were the most jealousy-evoking characteristic. Overall, the results indicate that transgender individuals mainly respond in line with their gender identity and not in line with their biological sex when facing romantic rivals. In addition, transgender individuals high in ISC experienced relatively more jealousy in response to all rival characteristics, whereas SCO was only among male-to-female individuals associated with jealousy.